Switched Beam Smart Antenna for Wireless Local Area Network - Evizal .; Sri Listia Rosa; Eko Supriyanto; Tharek Abd Rahman; Sharul Kamal Abdul Rahim; Ali Moradikordalivand (IAES Indonesia Section, 2014)
In wireless communication system, interference is one of the issue facing that can disturb in communicating between base station and mobile devices. This paper propose switched beam smart antenna system, an octagonal configuration of directional antenna is introduced and selecting beam to desire user. Each beam of antenna covered 45 degrees; by assembly of all directional antennas to create an omni-directional configuration with coverage all the beam 360 degrees. To control of the beam switching, an inexpensive microcontroller PIC 16F877 from microchip used, radio signal strength of mobile device receive as reference signal and compare to each of beam, the highest signal received is selected than microcontroller will lock to the desire beam. A few samples of received signal strength to be analysis by an algorithm to avoid multiple signals and select actual signal strength received. In this experiment 2.45 GHz ISM band used for the transmitter and receiver and testing have been conducted in outdoor environment. Results shows that switched beam smart antenna working fine base on mobile device location and able to switch the beam while mobile device is moving.